Clinical Outcomes of Acute Pancreatitis in Patients with Cirrhosis - Muhammad Irfan Shehzad, Mustaqeem Shah, Ikram Zada, Noman Kareem Qureshi, Shah Bakht Azeem, Amanullah Khokhar (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Acute Pancreatitis (AP) is a common disease requiring hospitalization. Though the mortality rate caused by pancreatitis decreased over the past few decades but patient’s organ failure causing mortality during acute pancreatitis is on the rise. The present study intended to assess the outcomes of acute pancreatitis in cirrhosis patients. Patients and Methods: This retrospective study was carried out on 180 acute pancreatitis patients admitted in the General Medicine and Gastroenterology Department of Central Hospital, Stadium Road Sargodha, Hayatabad Medical Complex Peshawar and Shaikh Khalifa bin Zayed Hospital, Muzaffarabad AJK for the duration from November 2021 to September 2022. Cirrhotic and non-cirrhotic patients were matched based on Propensity score matching (1:2). Inpatient mortality, systemic inflammatory response syndrome, length of hospital stay (LOS), and organ failure were the main outcomes. Model of End-stage Liver Disease (MELD) and Child-Pugh scores was used for cirrhotic patient’s subgroup analysis. Results: Of the total 180 AP patients, there were 60 cirrhotic (male 31 and females 29) and 120 (male 62 and females 58) non-cirrhotic patients. Based on Child-Pugh scores, the incidence of Child–Pugh scores A, B, and C was 17 (28.3%), 27 (45%), and 16 (26.7%) respectively. Based on cirrhosis etiology, the incidence of NAFLD (non-alcoholic fatty liver disease) , chronic hepatitis C, and autoimmune causes were 12 (20%), 42 (70%), and 6 (10%) respectively. Regarding diagnosis criteria, abdominal imaging diagnosed 56 (93.3%) patients whereas 4 (6.7%) were diagnosed based on liver biopsy. The mean BMI value in cirrhotic and non-cirrhotic groups was 28.4 and 26.8 kg/m2, p=0.51). Based on acute pancreatitis etiology, the incidence of gallstone-induced, idiopathic, and other in cirrhotic versus non-cirrhotic was 32 (53.3%) vs. 68 (56.7%), 12 (20%) vs. 30 (25%), and 16 (26.7%) and 22 (18.3%) respectively. Cirrhotic and non-cirrhotic patients’ outcomes such as inpatient mortality (6.8% vs. 1.7%), systemic inflammatory response syndrome (SIRS) (23.3% vs. 34.2%), and organ failure (13.3% vs 4.2%). Conclusion: The present study concluded the overall mortality and morbidity rates for cirrhotic and non-cirrhotic hospitalized with AP were similar. However, cirrhosis-related complications, portal hypertension and immunosuppression state such as sepsis, infections, and variceal bleed are likely to contribute to poorer outcomes and higher mortality compared to non-cirrhotic. Keywords: Acute pancreatitis, outcomes, acute liver injury